Verbal Process Analysis and Gender Placement of Selected Characters in Auwalu Yusuf Hamza’s A Day And A Half - Tifili , Delia Tijani (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
This paper seeks to carry out a verbal process analysis and gender placement in Auwalu Yusuf Hamza’s A Day and Half. Language is generally assumed to encourage and assist individuals in making alternative choices in utterance. Considering gender and worldview, individuals choose specific utterances to express their thoughts, feelings, and experiences, based on their gender, social and cultural backgrounds. The paper is knitted within the confines of Halliday’s Systemic Functional Grammar, it specifically handles the verbal process, which is one of the six (6) process types of transitivity in the ideational meta-function of language. Adopting the purposive sampling technique, the paper seeks to examine the following selected characters; Talele, Mairo, Kasimu and Iro. Mairo is presented as cruel, impolite and harsh towards Talele, who appears fragile, weak and confused. While Kasimu is presented as compassionate because he is in love with Talele; and Iro is jealous and angry towards Talele, because she refused to accept his love. Coming from a male author, the paper concludes that relegating women to the background; issues of gender inequality /equity, as conveyed through the use of language, is a norm where most communities are patrilineal.